Developing Social-Ecological System Approach and a Case Study in Red River Delta - Quang Hoc, Truong; Thi Ngoc Ha, Hoang (VNU Journal of Science: Policy and Management Studies, 2021)
After 3 decades of sustainable development, Vietnam's development is still not sustainable, especially in terms of society and ecology, the economy is still a brown economy: low product quality, high consumption resources, causing environmental pollution, increasing greenhouse gas emissions – causing climate change, and other social issues. In the last 20 years, the Socio-Ecological theory has developed on a global scale and is widely applied in many fields for sustainable development. Currently, Vietnam is having many innovations in the direction of rapid and sustainable development, nature-based/harmonization development, and planning based on integrated ecological functions, etc. In this direction, the Center for Eco-Community Development (ECODE) conducted a case study based on the Socio-Ecological system approach in 3 coastal districts (Tien Hai district, Thai Binh province, Giao Thuy district, Nam Dinh province, and Cat Hai district, Hai Phong city), typical for the Red River Delta – one of the areas in Vietnam most vulnerable to climate change, and has obtained significant results about: i) Zoning of social - ecological functions; ii) Assessing the impacts of climate change and development resources/climate disaster resilience of sub-regions; and iii) propose solutions and models of climate-adaptive livelihoods based on ecosystems. The research results confirmed the role of ecological and social pillars and systemic, interdisciplinary, inter-regional, and ecosystem-based approaches are crucial in research for sustainable development in the global context.